Texts from the Buddhist Canon, Commonly Known as Dhammapada with Accompanying Narratives - Beal, Samuel, (Brill | Manohar Publishers & Distributors, 2024)
Buddha's Dhammapada is a widely read scripture among the Buddhist followers. It plays a similar role as the Bible to Christianity, Gita to Hindus, Guru Granth Sahib to Sikhs, Torah to the Jews, and the Quran to the Muslims. The original version is contained in Khuddaka Nikaya, which is part of the Pali Theravada Buddhist Canons. Though Dhammapada was composed around the third century BCE, its traditions date back to the first century CE. It contains the sayings of Buddha in different situations, both to the monastic orders and others. Originally composed in Pali, there are different Dhammapadas , which were composed in Kharosthi, Buddhist Hybrid Sanskrit, Chinese, Tibetan, and Japanese. The Texts from the Buddhist Canon is the English translation of the Chinese version of Dhammapada , Fa Ju Jing.